E-business Diffusion in Hungarian SMEs: Challenges and Opportunities - Nemeslaki, András (Theory, Methodology, Practice – Review of Business and Management, 2007)
In this paper we introduce the main results of a survey describing the e-business adoption situation of Hungarian small and medium sized enterprises (SMEs). We used the e-w@tch methodology, and this enables European wide comparison of the status of e-business applications, but does not explain how individual SMEs might take advantage on using ICT resources. Therefore, we propose a theoretical framework based upon recent research, in order to better understand the e-business value creation process. We outline a multi-layer model where the value creation process is in the core, and several environmental factors exort their influence. We demonstrate the impacts of the macro level economical environment and the influence industrial sectors. After that, going deeper to the corporate level – in our cases we were mainly focusing on SMEs – we refer to the importance of using the concepts of online information capabilities and digital options to transform ICT resource toward organizational outputs. In the last section of our paper we used the EU-5 2003 and the 2004 Hungarian SME e-business adoption measurement to specify the resource side of the European e-business value creation. We found that the resource specifications are rather consistent, and concentrate around six groups of e-business resources: communication, remote access, complex ICTs, operational efficiency, knowledge and content management, and on-line sales resources.